Grainyhead-like 2 (GRHL2) knockout abolishes oral cancer development through reciprocal regulation of the MAP kinase and TGF-β signaling pathways - Wei Chen; Kyung L. Kang; Abdullah Alshaikh; Saaket Varma; Yi-Ling Lin; Ki-Hyuk Shin; Reuben Kim; Cun-Yu Wang; No-Hee Park; Katharina Walentin; Kai M. Schmidt-Ott; Mo K. Kang (Oncogenesis, 2018)
Abstract Grainyhead-Like 2 (GRHL2) is an epithelial-specific transcription factor that regulates epithelial morphogenesis and differentiation. Prior studies suggested inverse regulation between GRHL2 and TGF-β in epithelial plasticity and potential carcinogenesis. Here, we report the role of GRHL2 in oral carcinogenesis in vivo using a novel Grhl2 knockout (KO) mouse model and the underlying mechanism involving its functional interaction with TGF-β signaling. We developed epithelial-specific Grhl2 conditional KO mice by crossing Grhl2 floxed mice with those expressing CreER driven by the K14 promoter. After induction of Grhl2 KO, we confirmed the loss of GRHL2 and its target proteins, while Grhl2 KO strongly induced TGF-β signaling molecules. When exposed to 4-nitroquinoline 1-oxide (4-NQO), a strong chemical carcinogen, Grhl2 wild-type (WT) mice developed rampant oral tongue tumors, while Grhl2 KO mice completely abolished tumor development. In cultured oral squamous cell carcinoma (OSCC) cell lines, TGF-β signaling was notably induced by GRHL2 knockdown while being suppressed by GRHL2 overexpression. GRHL2 knockdown or KO in vitro and in vivo, respectively, led to loss of active p-Erk1/2 and p-JNK MAP kinase levels; moreover, ectopic overexpression of GRHL2 strongly induced the MAP kinase activation. Furthermore, the suppressive effect of GRHL2 on TGF-β signaling was diminished in cells exposed to Erk and JNK inhibitors. These data indicate that GRHL2 activates the Erk and JNK MAP kinases, which in turn suppresses the TGF -β signaling. This novel signaling represents an alternative pathway by which GRHL2 regulates carcinogenesis, and is distinct from the direct transcriptional regulation by GRHL2 binding at its target gene promoters, e.g., E-cadherin, hTERT, p63, and miR-200 family genes. Taken together, the current study provides the first genetic evidence to support the role of GRHL2 in carcinogenesis and the underlying novel mechanism that involves the functional interaction between GRHL2 and TGF-β signaling through the MAPK pathways.